2018
DOI: 10.1364/oe.26.019921
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interference as signature of atomic stabilization

Abstract: We study the ionization of atoms by very intense linearly polarized pulse with moderately high frequency by numerically solving the time-dependent Schrödinger equation (TDSE). In this regime, the photon energy exceeds the ionization potential allowing for one-photon ionization which is, however, strongly influenced by strong nonlinear photon-atom interactions. We find that the onset of atomic stabilization can be monitored by the appearance of a dynamic interference pattern in the photoelectron spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 47 publications
7
47
0
2
Order By: Relevance
“…However, the single peak can gradually evolve into a multi-peak structure due to the dynamic interference when the laser intensity is increased. The condi-tions to observe such a dynamic interference are recently discussed [13,15]. In fact, to observe the dynamic interference in the ground state of hydrogen at a moderately high laser frequency (∼50 eV), the peak intensity needs to be high enough (above 10 18 W/cm 2 ) for the atomic stabilization to occur [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the single peak can gradually evolve into a multi-peak structure due to the dynamic interference when the laser intensity is increased. The condi-tions to observe such a dynamic interference are recently discussed [13,15]. In fact, to observe the dynamic interference in the ground state of hydrogen at a moderately high laser frequency (∼50 eV), the peak intensity needs to be high enough (above 10 18 W/cm 2 ) for the atomic stabilization to occur [15].…”
Section: Introductionmentioning
confidence: 99%
“…The condi-tions to observe such a dynamic interference are recently discussed [13,15]. In fact, to observe the dynamic interference in the ground state of hydrogen at a moderately high laser frequency (∼50 eV), the peak intensity needs to be high enough (above 10 18 W/cm 2 ) for the atomic stabilization to occur [15]. The relative theoretical studies are presently limited to the dipole approximation for the laser-atom interaction.…”
Section: Introductionmentioning
confidence: 99%
“…A közelmúltban több kutatócsoport tagjai is rámutattak arra, hogy erős lézertérbe helyezett atomok és molekulák fotoelektron spektrumában egy küszöb lézer intenzitás felett az intenzitás növelésével a spektrumbeli csúcsok újfajta, egyre gazdagodó struktúrát mutatnak [1][2][3][4][5][6]. Az egyszerű fotocsúcsokon megjelenő interferencia mintázatért az alkalmazott lézerpulzus felszálló és leszálló ágában ionizált elektronok interferenciája a felelős [2].…”
Section: Bevezetésunclassified
“…A dinamikus interferenciát a keletkezés mechanizmusa szerint két alapvető csoportra oszthatjuk: i) direkt egyfotonos ionizációban (ℏω > I p ) létrejövő [1][2][3][4], valamint ii) köztes rezonáns állapotokon keresztül végbemenő (ℏω < I p ) ionizáció során keletkező dinamikus interferenciát [5][6] különböztethetünk meg. Az utóbbi esetben legalább két foton szükséges a rendszer ionizációjához.…”
Section: Bevezetésunclassified
“…Morales et al identified specific fine structures in photoelectron momentum distribution contributed by excited KH states [22]. Jiang et al suggested that the photoelectron momentum distribution carrying dynamical interference structures provides information on adiabatic stabilization [23]. However, these proposals are sensitive either to the laser intensity or to the pulse envelope and are not robust against ionization depletion.…”
mentioning
confidence: 99%